TANGGUNG JAWAB LINGKUNGAN DAN INFORMASI BIAYA LINGKUNGAN DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN - Andayani Andayani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The aim of this research is to know the company’s environmental responsibility, the opinion of the internal accountant to information which has to do with environmental costs and the types of environmental costs is considered important, and also the use of the environmental cost information in taking management decisions.The type of this research is qualitative, and this research is done in PT SIER (Persero), PT SDM Lab., and PT HMS, Tbk. Data is collected by questionnaire, interview, observation, and documentation. Interview is done with the internal accountant, financial manager, and company’s production manager, or the side who represent.The result of this research shows that the company’s environmental responsibility can be known through the result of measurement of environmental performance by identifying through the key elements ISO 14001. The company’s internal accountant has the opinion that environmental costs are the costs which  related to company production process and product influencing company net profit, also costs related to society, company community. Some type of environmental costs were said very important although according to spectrum of environmental costs is stated to have very difficult level in measuring. It happened because there is no the standard of accounting that arrange the problem of environmental reporting and measurement. The company’s internal accountant can play an important role in transforming the data become information about environment by identification environmental costs that is important, informing it as cost information, and integrating the costs in management decisions. Whether or not a cost is environmental, the goal is to ensure that relevant costs receive appropriate attention.